Ultraviolet-C light inactivation of Penicillium expansum on fruit surfaces. (April 2015) - Syamaladevi, Roopesh M.; Adhikari, Achyut; Lupien, Shari L.; Dugan, Frank; Bhunia, Kanishka; Dhingra, Amit; Sablani, Shyam S.
Abstract: Understanding the influence of fruit surface morphology on ultraviolet-C (UV-C 254 nm) inactivation of microorganisms is required for designing effective treatment systems. In this study, we analyzed UV-C inactivation of Penicillium expansum that was inoculated onto the surface of organic fruits. Results show that maximum reductions of 1.8 (apple), 2.4 (cherry), 2.6 (strawberry) and 2.8 (raspberry) log CFU/g were observed after 1.2, 2.1, 3.3, and 3.3 kJ/m 2 of UV-C doses, respectively. The UV doses required to reduce 2 log CFU/g of P. expansum population on apples, cherries, strawberries, and raspberries estimated with the Weibull equation were 1.03, 1.28, 1.39, and 1.61 kJ/m 2, respectively. Findings also show that the hydrophobic nature of raspberries, along with high surface roughness, resulted in a lower inactivation rate of P. expansum . This study shows that UV-C effectively reduces P. expansum populations on fresh fruit surfaces; however, the efficacy of treatment is dependent on fruit surface morphology. Highlights: UV-C light treatment significantly reduced the Penicillium expansum population on fruit surfaces. Fruit surface roughness and hydrophobicity influenced the effectiveness of UV-C on reducing the P. expansum population. UV-C doses to reduce 2 log CFU/g of P. expansum population did not change the color and soluble solid contents of fruits.